High performance wideband CMOS current conveyor for low voltage low power applications - Abolila, A H M; Hamed, H F A; Hasaneen, El-Sayed A M (The 10th IEEE International Symposium on Signal Processing and Information Technology, 2010)
New low voltage low power CMOS current conveyor (CCII) is presented. The proposed CCII is based on rail-to-rail class AB folded cascode operational amplifier. The new CCII provides very low input impedance at X-port, very high input impedance at Y-port, accurate voltage and current tracking with low offset, and very wide bandwidth. As an application, an oscillator has been built based on the proposed CCII. The performance of the proposed CCII has been confirmed by PSPICE simulation program using TSMC MOSIS 0.18 μm CMOS technology. The presented CCII is supplied at ± 0.75 V.